Chemical composition and microbial loads of chicken table eggs from retail markets in urban settings of Eastern Ethiopia - Senbeta, Ewonetu Kebede; Zeleke, Negasi Ameha; Molla, Yitbarek Getachew (Journal of Advanced Veterinary and Animal Research, 2015)
For the determination of microbial load, chemical quality, pH and cholesterol level, a total of 400 table eggs were randomly collected from 10 retailers situated at major urban settings in Eastern Ethiopia and Haramaya University Poultry Farm, Ethiopia. The data were analyzed using SAS. High moisture and cholesterol levels and low pH and huge microbial load were detected in the eggs. Exposure of eggs to sunlight in the market and transportation of eggs from farm to the retail market might influence in lowering moisture and increasing pH. Huge microbial contamination of eggs from retailers at urban settings could be due to unhygienic handling of the eggs, lack of standard storage and transportation facilities. Storing of eggs in refrigeration condition and protection of direct sun light could be helpful in maintaining quality eggs. Introduction of refrigeration systems and construction of shades in markets are suggested to maintain and improve quality of eggs sold in markets. http://dx.doi.org/10.5455/javar.2015.b108